Colección, cultivo y comportamiento agroecológico de nueve especies de plantas medicinales en el cantón Machala - Jaramillo Marín, José Andrés (2008)
During May to October, 2008 at Santa Inés Farm of the Technical of Machala a study about the agronomic characteristics of nine species of medicinal plants was carried out. These plants were collected from rural and suburban areas of the plains of the province of El Oro. The objectives of the present research were: 1). – To Collect, cultivate and determine the agro-ecological behavior of species of medicinal plants in the County of Machala. 2). – To spread the results through newsletters to the academic community. The genetic materials used were seeds and stolons of the following species: Albahaca, Basil (Ocimun basilicum L.), Ruda, Rue (Ruta graveolens), Toronjil, Lemon balm (Melissa officinalis L.), Orégano, Oregano (Origanium vulgare), Hierbabuena, Good herb (Menta crispa L.), Llantén, Greater Plantago (Plantago major L.), Paico, Mexican seed (Chenopodium ambrosioides L.), Menta, Peppermint (Mentha x piperita L.) and Jenjibre, Ginger (Zingiber officinale Roscoe). The germ plasma, seeds, and vegetative material were planted into experimental lots following agronomic standards. Setting spaces between ditches and the appropriate places for foliation, paying attention to the soil. The results of the experiment showed that all the species were acclimated and adjusted to agronomic handle long ago because the growth in the soil was satisfactory. They reached high levels of germination and sprouting of the vegetative parts up to 83% and even higher. According to growth and blossoming the species are grouped with the earlier species such as: greater plantago, basil, and lemon balm; and the semi-late species such as: Mexican seed, peppermint, and good herb, and at last the late species such as: ginger, oregano, and rue. On the other hand, the species differ from each other according to their capacity of growth and production of dry matter. The content of dry matter varied between 22.58% of the Basil and 50% of the (name). The production of biomass per hectare was increased from a sample of ten plants that covered an area of 2.4 square meters. It corresponds to the density of sowing with 6.0m between ditches and 0.40m between places of sowing. It is visualized that the basil, Mexican seed, and greater plantago produce greater biomass.